Effect of incorporating clustered silica nanoparticles on the performance and biocompatibility of catechol-containing PEG-based bioadhesive. (24th January 2018) - Pinnaratip, Rattapol; Meng, Hao; Rajachar, Rupak M; Lee, Bruce P
Abstract: A composite adhesive capable of inducing cellular infiltration was prepared by incorporating control clustered silica microparticle (MP) derived from the aggregation of silica nanoparticle (NP) into a catechol-terminated poly(ethylene glycol) bioadhesive (PEG-DA). Incorporation of MP into PEG-DA significantly improved the mechanical and adhesive properties of the bioadhesive. There was no statistical difference between the measured values for NP- and MP-incorporated adhesives, indicating that MP was equally as effective in enhancing the material properties of PEG-DA as NP. Most importantly, MP was significantly less cytotoxic when compared to NP when these particles were directly exposed to L929 fibroblast. When the adhesives were implanted subcutaneously in rats, MP-containing PEG-DA also exhibited reduced inflammatory responses, attracted elevated levels of regenerative M2 macrophage to its interface, and promoted cellular infiltration due to increased porosity within the adhesive network. Control clustered silica MP can be used to improve the performance and biocompatibility of PEG-based adhesive while minimizing undesirable cytotoxicity of silica NP.